2022
DOI: 10.3389/fvets.2022.931643
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and associated risk factors for foot and mouth disease virus seropositivity in cattle in selected districts of Gamo zone, Southern Ethiopia

Abstract: BackgroundFoot and mouth disease (FMD) is a highly contagious viral disease of cloven-hoofed animals, which hampers livestock production and productivity in Ethiopia. This cross-sectional study was conducted from January to December 2021 to estimate the seroprevalence of FMD in cattle and to assess farmers' knowledge about the disease in selected districts of the Gamo zone. Three districts and two kebeles (smallest administrative division) from each district were purposively sampled using a simple random sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…Our results show that adults are more affected with FMD than younger animals in Kafta Humera districts. Similar reports have been observed in Gamo Zone, southern Ethiopia ( 37 ). This can be due to calves being protected by passive maternal immunity and age-related physiological factors ( 37 ), and calves in this area have limited access to grazing until the age of 2 years.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results show that adults are more affected with FMD than younger animals in Kafta Humera districts. Similar reports have been observed in Gamo Zone, southern Ethiopia ( 37 ). This can be due to calves being protected by passive maternal immunity and age-related physiological factors ( 37 ), and calves in this area have limited access to grazing until the age of 2 years.…”
Section: Discussionsupporting
confidence: 90%
“…Similar reports have been observed in Gamo Zone, southern Ethiopia ( 37 ). This can be due to calves being protected by passive maternal immunity and age-related physiological factors ( 37 ), and calves in this area have limited access to grazing until the age of 2 years. We also found that, in Kafta Humera, females were more affected than males, an observation that was not reported in the Seharti Samre district.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[ 27 ]. However, some studies have reported significant differences between different age groups of animals with FMDV infection [ 28 ]. All age groups are susceptible to FMDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…This necessitates advanced statistical methods and tools for estimating the sero-prevalence rate at population-level using test results from NSP-ELISA. However, attempts have been made to estimate the FMDV sero-prevalence through cross sectional sample-based sero-surveillance in cattle 29 , 33 , 34 and small ruminants 29 in Ethiopia, cattle and wild life in Nigeria 35 , wild life and buffalo population in eastern Africa 36 , small ruminants in Kenya 2 , etc. In all these studies, the sero-prevalence results were limited to sample proportions (e.g., total sample: 384; positive sample: 76; sero-prevalence rate: 19.79%) 29 , 33 36 without going for country-level estimate of FMDV sero-prevalence rate.…”
Section: Introductionmentioning
confidence: 99%